Case Report: Takotsubo Syndrome Associated With Novel Coronavirus Disease 2019 - Ortuno, Sofia; Jozwiak, Mathieu; Mira, Jean-Paul; Nguyen, Lee S. (Frontiers in Cardiovascular Medicine, 2021)
Background Tako-Tsubo cardiomyopathy is triggered by emotional or physical stress. It is defined as a reversible myocardial dysfunction, usually with apical ballooning aspect due to apical akinesia associated with hyperkinetic basal left ventricular contraction. Described in cases of viral infections such as influenza, only few have been reported associated with Covid-19 in the recent pandemic. Case summary A 79-years-old man, with cardiovascular risk factors (type 2 diabetes and hypertension) and chronic kidney disease presented to the emergency room for severe dyspnea after 8 days of presenting respiratory symptoms and fever. Baseline electrocardiogram (EKG) was normal, he presented marked inflammatory syndrome. He was transferred to an intensive care unit to receive mechanical ventilation within 6 hours, due to acute respiratory distress syndrome. He presented circulatory failure 2 days after, requiring norepinephrine support (up to up to 1.04 µg/kg/min). Troponin T was elevated (637 ng/L). EKG showed diffuse T wave inversion. Echocardiography showed reduced left ventricular ejection fraction (LVEF 40%), with visual signs of Tako-Tsubo cardiomyopathy. Cardiac failure resolved after 24 hours with troponin T decrease (433 ng/L) and restoration of cardiac function (LVEF 60% with regression of Tako-Tsubo features). Patient died after 15 days of ICU admission, due to septic shock from ventilator-acquired pneumonia. Cardiac function was then normal. Conclusion Mechanisms of Tako-Tsubo cardiomyopathy in viral infections include catecholamine-induced myocardial toxicity and inflammation related to sepsis. Differential diagnoses include myocarditis and myocardial infarction. Evidence of benefit of immunomodulatory drugs and dexamethasone are growing to support this hypothesis in Covid-19.